2
p - 1
p + 1
2p - 2
2p + 1
Correct answer is E
2p2 - 2
2(p2 - 1)
= 2(p + 1)(p - 1)
If f(x) = 2(x - 3)2 + 3(x - 3) + 4 and g(y) = √5+y, find g [f(3)] and f[g(4)]....
In the diagram, EF//QR, PE = 2cm, EQ = 4cm and FR = 6cm. Find x ...
If the volume of a hemisphere is increasing at a steady rate of 18π m3 s−1, at what...
Given that A and B are sets such that n(A) = 8, n(B)=12 and n(AnB) =3, find n(AuB). ...
A fair die is tossed twice what is the probability of get a sum of at least 10. ...
What must be added to the expression x2 - 18x to make it a perfect square?...
Which of the following could be the inequality illustrated in the sketch graph above? ...